“I Sing the Poet Electric” - Robertson, Judith P. (Journal of the Canadian Association for Curriculum Studies, 2012)
The poetry that follows was born in the slippages between pedagogy and art, memory and desire, chaos and learning. Through the gestures of poetic language, I explore fragilities tied to times of learning, the conflicts of academic identity, and being touched and calling out in turn. Initially performed under the aegis of “I Sing the Poet Electric” at Aprés Vous, a Canadian symposium organized in November 2012 at OISE in tribute to the extraordinary work of Professor Emeritus Roger Simon, the poems are given in loving memory of the ongoing power of affect of his singular demands and teachings.